If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -21q = -3q + 2(-5q + -2) Reorder the terms: 10 + -21q = -3q + 2(-2 + -5q) 10 + -21q = -3q + (-2 * 2 + -5q * 2) 10 + -21q = -3q + (-4 + -10q) Reorder the terms: 10 + -21q = -4 + -3q + -10q Combine like terms: -3q + -10q = -13q 10 + -21q = -4 + -13q Solving 10 + -21q = -4 + -13q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '13q' to each side of the equation. 10 + -21q + 13q = -4 + -13q + 13q Combine like terms: -21q + 13q = -8q 10 + -8q = -4 + -13q + 13q Combine like terms: -13q + 13q = 0 10 + -8q = -4 + 0 10 + -8q = -4 Add '-10' to each side of the equation. 10 + -10 + -8q = -4 + -10 Combine like terms: 10 + -10 = 0 0 + -8q = -4 + -10 -8q = -4 + -10 Combine like terms: -4 + -10 = -14 -8q = -14 Divide each side by '-8'. q = 1.75 Simplifying q = 1.75
| 9b+38=10b | | -6r-4(1+3r)=36+2r | | x/x+4=6/5 | | -2t-4=20 | | -328=-7(4-7x) | | 14=2x+4 | | 15=-3*2q-1 | | x/x^2-25=5/x^2-25-4/x+5 | | 27/5=-28k/5-1/5(-3k-2) | | x-1/5-1=x-7/4 | | (2x+3)=(5x-6) | | 5*a-1=35 | | X(5x-8)=(5x+4)(x-4) | | 5x/6-2=x/2+4 | | 4=5(s-2t) | | 1-16x^4=0 | | 8y-3y-4=21 | | 6x-10=5x-4 | | 2x+3(x-3)=36 | | 4n/3-5/7=97/21 | | (8x+5)/(10x-7)=(4x+3)/(5x+7) | | 2*1725=m+1/2m | | 38=4x+3(2x-4) | | 25+x=9 | | 2x/5-4=12 | | 4x+2(x-2)=26 | | 13ab+1(-12ab)= | | 3x+2(x+4)=53 | | 3/4(24-8a)=2(5a+1) | | 4-a=9 | | (1-x)((2-x)(1-x)-1)-1((1-x)-2)+2(1-2(2-x))=0 | | (4)/(x-1)+(6)/(3x+1)=(15)/(3x+1) |